FURTHER OBSERVATION ON THE BASIC DESIGN OF BRAIN PATTERN IN SOME TELEOSTS - PANDEY, K. C.; SINGH, H. S.; KUMAR, YOUGESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
During present investigation authors have stressed upon the brain pattern and some salient features of brain faculties in certain teleostean fishes. General plan of nervous system and considerable difference in relative development of different regions of brain and their significance towards nervous activity have been referred at the same.